Satisfaction as the Moderator Between Discrimination and Stress at Work - Adhikari, Pralhad (Tribhuvan University Journal, 2022)
Job satisfaction refers to the positive emotions an employee gets from various aspects of their work. Work-related stress is the stress caused because of one’s job. Work discrimination is the perception of being treated unfairly at work. Job satisfaction has the chance of being protective against work-related stress caused by discrimination at work. An online survey was developed in Google Forms to test the hypothesis that job satisfaction moderated the relationship between work discrimination and work stress among Nepalese employees. A snowball sample of 278 employees working in various professions was made in the first three months of 2022. Moderation analysis was done and the results showed that highland average but low levels of job satisfaction were protective against the work stress caused by discrimination at work. One-fourth of employees were found to have job satisfaction. Job satisfaction was significantly negatively associated with discrimination and stress at work. The conclusion is that the employers should try to increase job satisfaction of the employees in workplaces where there is more discrimination to protect employees against negative consequences of work-related stress. In the future, studies focused on specific occupations can be carried out to test the same hypothesis.